新加坡华语口语重叠式研究 = A study of reduplication in spoken Singapore Mandarin - 蔡佳馨 Chua, Kah Hsing (2015)
新加坡华语作为现代汉语的一种变体，在许多方面都有其特殊之处，而重叠便是其中一个方面。现今学界对于现代汉语重叠式的研究已相当成熟且丰富，但相比之下，新加坡华语口语的重叠式研究则稍显不够完善。因此，本文旨在深入且系统地探讨新加坡华语口语重叠式的可重叠范围、表达的语法意义和语用功能。目前为止，新加坡还未有一个实用的口语语料库，因此，笔者决定连同其他三位本科生一起建立一个口语语料库。本文大部分的新加坡华语口语重叠式例子和例句都是取自这个口语语料库。另外，本文除了利用口语语料库的数据分析重叠式之外，也将额外以问卷调查的形式，考察新加坡华语“VV一下”这一特殊结构。总的来说，通过本次研究，笔者发现新加坡特殊的重叠式主要集中在动词重叠、形容词重叠及名词重叠。其中，新加坡特殊的形容词重叠式出现的频率最高。此外，大多的特殊重叠式是受到闽南语的影响而形成的。Singapore Mandarin is, in many ways, different from the standard Modern Chinese, and reduplication is one of the aspects where Singapore Mandarin has exhibited its distinctiveness. Today, there exist many in-depth studies on reduplication in Modern Chinese. Yet, the study of reduplication in Singapore Mandarin paled in comparison. As such, this thesis aims to provide a systematic and thorough investigation on the scope, grammatical meaning and pragmatic functions of reduplications in Singapore Mandarin. As Singapore lacks database of spoken Singapore Mandarin, the author, along with 3 other undergraduates majoring in Chinese, constructed a corpus of spoken Singapore Mandarin together for the purpose of this study. In addition to the corpus data, a survey was also conducted to investigate the “VV yixia” structure that is exclusive to Singapore Mandarin. All in all, through this study, it was found that the unique forms of reduplication in Singapore Mandarin are mainly reduplicated verb, reduplicated adjective and reduplicated noun. Among the three, reduplicated adjective has the highest number of unique forms. It was also found that the unique reduplications were mostly influenced by the Hokkien dialect in Singapore.